2016
DOI: 10.3892/br.2016.626
|View full text |Cite
|
Sign up to set email alerts
|

Role of exercise in the treatment of alcohol use disorders

Abstract: Excessive alcohol use can cause harmful effects on the human body, which are associated with serious health problems, and it can also lead to the development of alcohol use disorders (AUDs). There is certain evidence that physical exercise positively affects excessive alcohol use and the associated problems by leading to reduced alcohol intake. A literature search was conducted using the databases PubMed, Medline and Web of Science. The search terms used as keywords were: Addiction, abuse, alcohol use disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 54 publications
1
35
0
3
Order By: Relevance
“…Exercise interventions in AUDs were considered safe, with no adverse events reported. Manthou et al 23 examined studies reporting the use of exercise to treat AUDs published between 1970 and 2015, including the underlying mechanisms. In total, 11 studies were identified, of which six concluded that exercise may have a positive impact on consumption, abstinence rates or the urge to drink 23.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise interventions in AUDs were considered safe, with no adverse events reported. Manthou et al 23 examined studies reporting the use of exercise to treat AUDs published between 1970 and 2015, including the underlying mechanisms. In total, 11 studies were identified, of which six concluded that exercise may have a positive impact on consumption, abstinence rates or the urge to drink 23.…”
Section: Introductionmentioning
confidence: 99%
“…11 studies were identified to refer the effect of exercise on alcohol consumption and associated outcomes. Six of these concluded that exercise may have a positive impact towards alcohol consumption 6 . Each domain in the quality of life also showed significant changes in experimental group than control group.…”
Section: Discussionmentioning
confidence: 99%
“…This method of treatment is often used with patients with serious problems orwith patients with less serious alcohol problems (13).…”
Section: ) Overview Of the Studies Finally Included Is Presented As mentioning
confidence: 99%